Impact of Column Force on The Slope of a Gable Frame Roof - Arini, Resti Nur Arini; Haykal, Fadel Muhammad; Kurni, Fadli; Ariyani, Dwi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
One structure utilized in commercial and industrial buildings is the gable frame. This frame is tapered with slopes on both sides, making it a sturdy and effective construction. Since the stability of the rigid frame must be ensured by using gable frames, internal forces impact the frame's stability. Additionally, gable frames are made to support various kinds of loads. By analyzing the cross-sectional area and inertia that give rigidity to the size of the beams and columns in each element, the structure may be made more flexible. The impact of internal forces on the column on changes in roof slope will be analyzed as part of this study. To analyze the effect of columns on roof slopes, gable frame modeling is done using the STAAD Pro aid program, and the profile utilized is IWF 588x300x12x12. The 5o, 7o, 10o, 15o, and 20o slope variations are used to observe the impact of internal forces that occur in shape within the column for the Load and Resistance Factor Design (LRFD) method of cross-section control calculation analysis. SNI 1727:2020 is used for cross-section checks, and 17226:2019 is used for load calculations. According to the modeling results, a considerable axial force will be produced at a slope of 20 degrees. In contrast, a lesser slope angle will result in larger compressive and tensile stress, namely at a slope of 5 degrees. The gable frame's use of slope will impact the axial force by 4%.